Hubungan Kadar Kadmium (Cd) dalam Rambut dengan Kadar Asam Urat pada Pekerja Las di Kelurahan Banaran, Kecamatan Grogol, Kabupaten Sukoharjo - Pradita Isdio Mahendra Renza; Mastuti Widi Lestari (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2023)
Welding workers are potentially exposed to cadmium containing fumes during the welding process. Cadmium is one of the heavy metals that is considered toxic. Cadmium heavy metals can interfere with the health of body organs such as the kidneys. Accumulation of cadmium in the kidneys can decrease the excretory activity of the veins. Resulting impact is an increase in uric acid levels in the body (hyperuricemia). This study aims to determine the relationship between cadmium levels in hair and uric acid levels of welding workers in Kelurahan Banaran, Kecamatan Grogol, Kabupaten Sukoharjo. Study was conducted using a purposive sampling method on 15 male welding workers. Cadmium levels in the hair were examined using FAAS. Uric acid levels in capillary blood are checked using POCT. Results of the examination of cadmium levels in 15 samples were still within the limits set by Biolab <0.10 ppm. Uric acid content examination results obtained 2 of the 15 samples had high uric acid levels >7.2 mg/dl. Data were analyzed using SPSS Pearson's Correlation Test. Results of the Pearson correlation test showed that there was no relationship between cadmium levels in the hair and uric acid levels in welding workers in Kelurahan Banaran, Kecamatan Grogol, Kabupaten Sukoharjo.Keywords: Uric Acid, Cadmium, Pearson Correlation, Welding Workers